2013
DOI: 10.1371/journal.pone.0064034
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-Derived Oxidants Induce Blood-Brain Barrier Dysfunction In Vitro and In Vivo

Abstract: Peripheral leukocytes can exacerbate brain damage by release of cytotoxic mediators that disrupt blood-brain barrier (BBB) function. One of the oxidants released by activated leukocytes is hypochlorous acid (HOCl) formed via the myeloperoxidase (MPO)-H2O2-Cl− system. In the present study we examined the role of leukocyte activation, leukocyte-derived MPO and MPO-generated oxidants on BBB function in vitro and in vivo. In a mouse model of lipopolysaccharide (LPS)-induced systemic inflammation, neutrophils that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 60 publications
3
53
0
Order By: Relevance
“…In the same experiment, we showed that the BBB was completely sealed after five days of MPO inhibition [122]. Further data supporting a role for MPO in opening of the BBB is a study that transiently opened the barrier by LPS injection, which lead to significantly less CNS vascular permeability in Mpo − / − mice as compared to WT [120]. Cumulatively, these data suggest a role for neutrophil-derived MPO in the breakdown of the BBB contributing to MS disease progression in the absence of a direct impact on adaptive immunity.…”
Section: Mpo In Multiple Sclerosis (Ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same experiment, we showed that the BBB was completely sealed after five days of MPO inhibition [122]. Further data supporting a role for MPO in opening of the BBB is a study that transiently opened the barrier by LPS injection, which lead to significantly less CNS vascular permeability in Mpo − / − mice as compared to WT [120]. Cumulatively, these data suggest a role for neutrophil-derived MPO in the breakdown of the BBB contributing to MS disease progression in the absence of a direct impact on adaptive immunity.…”
Section: Mpo In Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Using a primary brain microvascular endothelial cell line, it was shown that MPO can directly alter permeability in vitro [120]. In our studies utilizing the novel MPO inhibitor N -acetyl lysyltyrosylcysteine amide (KYC) [121], we found that its daily administration starting at disease initiation did not alter the day of onset or the kinetics of the first seven days of disease progression after which disease progression stalled resulting in a significantly reduced peak and cumulative disease score [122].…”
Section: Mpo In Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Previous studies have shown that Cl-lipids can elicit cell death in endothelial and neuronal cells, promote cell permeability leading to compromised blood-brain barrier, inhibit endothelial function by inhibiting eNOS-dependent signaling, and promote the inflammatory potential of endothelial cells, neutrophils, and macrophages (27,28,30,47,48). The precise mechanisms linking Cl-lipids to these responses remains under investigation, but modulation of MAPKs and perturbation of redox-signaling are likely candidates.…”
Section: Effects Of Cl-lipids Of Systemic Vascular Dilationmentioning
confidence: 99%
“…MPO can also induce endothelial dysfunction and inducible nitric oxide synthase (iNOS) upregulation leading to formation of peroxynitrite and "nitrative stress" aftermath.Recent experimental reports have revealed that MPO not only has catalytic activity but also exhibits cytokine-like properties, directly regulating inflammatory signaling cascades(84,90,91). Ullen et al, 2010 reported a LPS mediated BBB breakdown through multiple pathways, including the release of HOCl, formation of cytotoxic and signaling-active compounds like 2-chlorohexadecanal or indirectly by increasing inflammatory cell recruitment via electrostatic interaction of MPO with the brain endothelium thereby recruiting additional neutrophils(92,93). The involvement of MPO in BBB dysfunction was also associated with bacterial meningitis(93).…”
mentioning
confidence: 99%
“…Ullen et al, 2010 reported a LPS mediated BBB breakdown through multiple pathways, including the release of HOCl, formation of cytotoxic and signaling-active compounds like 2-chlorohexadecanal or indirectly by increasing inflammatory cell recruitment via electrostatic interaction of MPO with the brain endothelium thereby recruiting additional neutrophils(92,93). The involvement of MPO in BBB dysfunction was also associated with bacterial meningitis(93). Myeloperoxidase stimulates pro-inflammatory responses with release of cytokines like IL-1β, IL-6, IL-8, IFN-γ with concomitant increase in cellular "oxidative stress" which ensures the perpetuation of the inflammatory cascade, instigating chronic ROS production and cytokines release causing relentless worsening of the neurodegenerative process(94).…”
mentioning
confidence: 99%